Com‐On Questionnaire: Development and validation of a questionnaire for evaluating communication skills of oncologists. (19th August 2022) - Wuensch, Alexander; Boden, Maren J.; Pärschke, Pia P.; Peltzer, Samia; de Figueiredo, Marcelo Niglio; Bylund, Carma L.; Zimmer, Heinz; Vitinius, Frank
Abstract: Objective: The present study aimed to develop and validate an instrument for assessing the communication skills of oncology physicians from a patient's point of view. Methods: A first draft of the questionnaire was compiled based on skills reflecting good physician–patient communication identified in the literature. The questionnaire was critically revised by experts to ensure the validity of its contents. The revised questionnaire was completed by a sample of 153 cancer patients. The questionnaire was developed in German and later translated into English. Results: After analysis using classical test theory and an exploratory factor analysis, four different factors could be extracted. These factors were labelled setting, patient‐centeredness, empathy and consulting competencies. Unsuitable items were eliminated within the analysis. All remaining items hold an appropriate degree of selectivity, item difficulty and reliability/consistency. Conclusion: A novel questionnaire for evaluating communication skills of physicians was developed. It contains 36 items and is named 'Com‐On Questionnaire: Questionnaire for the Evaluation of Physician's Communication Skills in Oncology'. Practice Implications: The questionnaire is suitable for measuring both the strengths and deficits within the physician–patient communication in oncology from the patients' perspective.